The protective effect of PPARγ in sepsis-induced acute lung injury via inhibiting PTEN/β-catenin pathway. Issue 5 (28th May 2020) - Liu, Lili; Chen, Junyi; Zhang, Xiaofang; Cui, Xue; Qiao, Nana; Zhang, Yun; Yang, Jie
Abstract: The present study aims to reveal the molecular mechanism of peroxisome proliferator-activated receptor γ (PPARγ) on sepsis-induced acute lung injury (ALI). To do that, the rat injury model was established using cecal ligation and perforation (CLP) method, followed by different treatments, and the rats were divided into Sham group, CLP group, CLP + rosiglitazone (PPARγ agonist) group, CLP + GW9662 (PPARγ inhibitor) group, CLP + bpV (phosphatase and tensin homolog (PTEN) inhibitor) group, CLP + GW9662 + bpV group. Compared with Sham group, the mRNA and protein expression levels of PPARγ were down-regulated, the inflammation levels were elevated, and the apoptosis was increased in CLP group. After treatment with rosiglitazone, the protein expression level of PPARγ was significantly up-regulated, the phosphorylation level of PTEN/β-catenin pathway was decreased, the PTEN/β-catenin pathway was inhibited, the lung injury, inflammation and apoptosis were reduced. The opposite effect was observed after treatment with GW9662. Besides, bpV inhibited PTEN/β-catenin pathway, and relieved the lung tissue injury. The overexpression of PPARγ reduced inflammatory response and inhibited apoptosis in sepsis-induced ALI. Furthermore, PPARγ relieved the sepsis-induced ALI by inhibiting the PTEN/β-catenin pathway.